A dimensão do trágico na formação docente pela força estético-formativa do testemunho - Fagundes, André Luiz de Oliveira (2016)
This thesis was developed within the Research, Training, Knowledge and Professional Development Line (LP1), of the Postgraduate Program in Education, of the Education Center (CE), of the Federal University of Santa Maria (UFSM). The research unfolds from the following problematic: In a time of superficial understanding of the pain of others, how to recover the dimension of the tragic in teaching training, especially for what the potential of the literature of testimony, considered from an aesthetic and pedagogical dimension, can offer in terms of devices for the training process of the teacher in the context of post-traumatic social life? In these terms, the central aim of the thesis is: To recover and resignify the dimension of the tragic in teacher training, especially by what the aesthetic-affective force present in the testimonial work can lead to in a formation that is more involved with the humanity of the other. In more specific terms the objectives are: a) To undertake a critique of the presence of the epistemic-professional imperative in the scenario of teacher training, to the detriment of the broader training focused on concern for social justice, humanity on the other and human rights; b) To highlight, from historical bases, the importance of the tragic to the conception of human formation in its critical and aesthetic significance; c) Regarding the problem of human formation, highlight the theoretical and social imbrication between the idea of tragedy in the poetic-literary sense and the tragic sense as emanation of the polis and history; d) To elucidate the confluence between the category of the catastrophe and the expression of the tragic within the aesthetics present in the testimony, rethinking its implications in the context of the formative processes. The reasons for this work are justified by the idea that before setting the focus of teacher training in the concern with the list of skills and operational skills necessary to establish the idea of professionalization, we believe that it is vital to enter into a deeper and more essential aspect. Irremediably this leads to the reconfiguration of the teaching being, which, in turn, goes, according to the peculiarities of the present time, through the search for a re-signification of the tragic sense in the formation. The methodological orientation of the investigation follows the directions of the negative dialectic of Theodor Adorno.